IC 2395 and BH 47: only one open cluster in the Vela constellation - Claria Olmedo, Juan Jose (2003)
We report UBV photoelectric photometry for 273 stars in the fields of the open clusters IC 2395 and BH 47. Our postulate is that, rather than two different clusters in this region of Vela, there is only one, which we call IC 2395 = BH 47. The cluster is centered at about α = 8h42. m5, δ = −48◦06. 8 (2000), its angular diameter being ∼19 . The analysis of the photometric data yields 61 probable cluster members and 16 possible members. Photometric membership probabilities show good agreement with those obtained from a proper motion study for 21 stars in common. The reddening across the cluster appears to be uniform, the mean E(B − V) value being 0.09 ± 0.02. The true distance modulus is (V − MV )0 = 9.52 ± 0.10, corresponding to a distance from the Sun of (800 ± 40) pc and 48 pc below the Galactic plane. The cluster age, determined by fitting isochrones with core overshooting, turns out to be (6 ± 2) Myr. There is a strong likelihood that IC 2395 = BH 47 is physically connected to the Vela OB1C association.